2022
DOI: 10.1111/gcb.16446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of climate on salmonid productivity: A global meta‐analysis across freshwater ecosystems

Abstract: Salmonids are of immense socio-economic importance in much of the world, but are threatened by climate change. This has generated a substantial literature documenting the effects of climate variation on salmonid productivity in freshwater ecosystems, but there has been no global quantitative synthesis across studies. We conducted a systematic review and meta-analysis to gain quantitative insight into key factors shaping the effects of climate on salmonid productivity, ultimately collecting 1321 correlations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 214 publications
1
10
0
Order By: Relevance
“…Time series data of climate variables suggested that high temperatures and decreased summer flow may be limiting factors for trout populations in the southern regions of Sweden. Such findings are also in line with a recent global meta-analyses of 156 studies showing reduced salmonids productivity at low latitudes and elevations, likely caused by increased temperature and drought frequency, and increased productivity at high latitudes and elevations, where cold temperatures generally limit salmonid growth and abundance (Gallagher et al 2022). Our results point to the importance of considering thermal heterogeneity at regional and national scales when developing local prescriptions for management and conservation of species with broad distributional ranges, such as brown trout.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Time series data of climate variables suggested that high temperatures and decreased summer flow may be limiting factors for trout populations in the southern regions of Sweden. Such findings are also in line with a recent global meta-analyses of 156 studies showing reduced salmonids productivity at low latitudes and elevations, likely caused by increased temperature and drought frequency, and increased productivity at high latitudes and elevations, where cold temperatures generally limit salmonid growth and abundance (Gallagher et al 2022). Our results point to the importance of considering thermal heterogeneity at regional and national scales when developing local prescriptions for management and conservation of species with broad distributional ranges, such as brown trout.…”
Section: Discussionsupporting
confidence: 90%
“…This finding, which should be corroborated by future research, can have large implications for the management and conservation of salmonids. In a global meta‐analysis, Gallagher et al (2022) showed that increased precipitation during the growing season had a significantly higher negative effects on anadromous populations of salmonids compared to freshwater residents. In our study we found that abundance of juveniles of migrating brown trout populations, especially those migrating to the sea, showed sharper and more frequent declines in warmer regions than resident populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, stream temperatures in Cape Race are invariably shaped by the region's unusually cool and wet microclimate, which has few analogues throughout the native range of brook trout and may explain why the highest predicted stream temperatures in Cape Race (~17–19°C) were lower than similar studies conducted in Canada (~23–24°C in Quebec; Daigle et al., 2019) and the United States (~22–23°C in Virginia and Michigan; Carlson et al., 2019; Snyder et al., 2015). Therefore, while fine‐scale variation in groundwater contributions may influence stream thermal regimes throughout much of the species range, its consequences will depend on current and future climate conditions, with temperatures expected to exceed thermal optima more often in warmer regions at low latitudes and elevations (Gallagher et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulating discussions about thermal controls on salmonid populations in recent decades, of course, has been anthropogenic climate change that is increasing water temperatures globally (McCullough et al 2009;van Vliet et al 2013;O'Reilly et al 2015;Isaak et al 2018) and exacerbating habitat losses and productivity declines among salmonids and other aquatic species where warm conditions are limiting (Lynch et al 2016;Gallagher et al 2022). The potential for climate change to reduce the geographic extent occupied by salmonids was first recognized in late 20th-century bioclimatic assessments (Meisner 1990;Keleher and Rahel 1996;Nakano et al 1996), which spawned many similar studies (reviewed by ) and, more recently, case histories that document species distribution shifts consistent with model predictions (Hari et al 2006;Winfield et al 2010;Almodóvar et al 2012;Lemoine et al 2020;Bell et al 2021;Maitland and Latzka 2022;Svenning et al 2022).…”
Section: Introductionmentioning
confidence: 99%